Studies on double selenates. I. Thermal decomposition of lanthanum and alkali metal double selenates - Ionashiro, Massao [UNESP]; Giolito, I. (Elsevier, 1980)
Thermogravimetry, differential thermal analysis and other methods of analysis have been used to study the decomposition of hydrated lanthanum and alkali metal double selenates up to 1300°C. The results showed slight variations in the initial temperature of the various intermediate decomposition stages of the double selenates, as compared with the initial temperature of the corresponding decomposition of the simple selenates. The results also permitted the suggestion of mechanisms of thermal decomposition of these compounds. © 1980.